Perbedaan Kdar High Density Lipoprotein antara Penderita Ulkus Diabetik dan Tanpa Ulkus Diabetik pada Pasien Diabetes Melitus Tipe 2 di RSUD Dr. Moewardi - Muhammad, Apriyanda; , dr. Nur Hidayat, Sp. PD; , dr. Iin Novita Nurhidayati Mahmuda, M.Sc., Sp.PD (2015)
Diabetes mellitus (DM) was a disease that each year has increased. Increased prevalence of DM course will be followed by an increased risk of complications. DM complications one that often occurs was diabetic ulcers. Diabetic ulcers could occur as a result of several risk factors, including lipid profile, duration of diabetes mellitus, age, hypertension, etc. Risk factors that occured can leaded to atherosclerosis sustainable events into a diabetic ulcer. The formation of atherosclerosis was closely related to a decrease in High Density Lipoprotein levels (HDL) in patients with diabetes type 2. Objective: To determined whether there were differences in HDL levels in patients with diabetes type 2 with diabetic ulcers and without diabetic ulcers in Dr. Moewardi hospitals. Methods: This study was observational, cross sectional approach. Retrieving data used purposive sampling with a sample size of 20 patients diabetes mellitus with diabetic ulcers and 20 without diabetic ulcers. The analysis in this study using unpaired t-test. Results: There were differences between the mean levels of HDL were significantly between patients DM type 2 with diabetic ulcers and without diabetic ulcers the value of p = 0.002 (p <0.05). The mean levels of HDL in patients diabetes type 2 with diabetic ulcers reached 11.60 mg / dl while the average HDL in patients diabetes type 2 without diabetic ulcers reached 33.35 mg/dl Conclusions: There were differences in HDL levels significantly between patients diabetes type 2 with diabetic ulcers and without diabetic ulcers in Dr. Moewardi hospitals. Keywords: HDL, diabetic ulcer, Type 2 DM. 1The Student of Medical Faculty, Muhammadiyah Surakarta University 2The Lecturer of Medical Faculty, Muhammadiyah Surakarta University